2017
DOI: 10.1371/journal.pone.0179679
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the recent West Nile virus lineage 2 epidemic in Europe and Italy using discrete and continuous phylogeography

Abstract: West Nile virus lineage 2 (WNV-2) was mainly confined to sub-Saharan Africa until the early 2000s, when it was identified for the first time in Central Europe causing outbreaks of human and animal infection. The aim of this study was to reconstruct the origin and dispersion of WNV-2 in Central Europe and Italy on a phylodynamic and phylogeographical basis. To this aim, discrete and continuous space phylogeographical models were applied to a total of 33 newly characterised full-length viral genomes obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 44 publications
6
45
0
3
Order By: Relevance
“…These results were confirmed by the East–West geographical shift observed when plotting the cumulative distribution curves of WNND cases by longitude. Interestingly, similar results have been found by a phylogenetic analysis conducted among humans, mosquitoes and birds, which underlined that the WNV spatial spread observed in Northern Italy in recent years probably occurred along the Po river and its main tributaries with an East–West gradient (Zehender et al, ). These results suggest that Po River and its neighbouring areas might present environmental and ecological conditions that can promote WNV transmission and circulation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results were confirmed by the East–West geographical shift observed when plotting the cumulative distribution curves of WNND cases by longitude. Interestingly, similar results have been found by a phylogenetic analysis conducted among humans, mosquitoes and birds, which underlined that the WNV spatial spread observed in Northern Italy in recent years probably occurred along the Po river and its main tributaries with an East–West gradient (Zehender et al, ). These results suggest that Po River and its neighbouring areas might present environmental and ecological conditions that can promote WNV transmission and circulation.…”
Section: Discussionsupporting
confidence: 76%
“…Once introduced in new areas by infected migratory birds, WNV must establish an endemic cycle of transmission among immunologically naïve birds and mosquitoes (Chancey et al, ). It has been shown that the virus can circulate among reservoirs and vectors for several years before causing significant human outbreaks (Zehender et al, ). It has been hypothesized that the persistence of the virus in new affected areas might be due to infected birds that develop persistent WNV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this country, significant seroprevalence levels have recently been described in humans with meningitis and lymphocytic meningitis (14 of 42 cases), as well as in horses and wild birds [44]. Finally, as suggested by Zehender et al [61], WNV may need a few years of enzootic circulation before transmission to dead-end hosts: Poland may be in this situation. This time lag may be partially explained by the above–mentioned conjectural risk and justify a long term surveillance and awareness in risky areas.…”
Section: Discussionmentioning
confidence: 99%
“…The d N /d S ratios for all genes in WNV-2 Europe are higher than those in WNV-1 except NS4A and also those in WNV-2 Africa except NS5, suggesting that WNV-2 European has a smaller N e than WNV-1 and WNV-2 Africa and/or the effect of negative selection has not been fully accumulated (rule 5). Note that WNV-2 Europe is likely a young strain, as it was transmitted to Europe probably in early 21st century (24).…”
Section: Significancementioning
confidence: 99%